IMPLEMENTASI UU NO.21 TAHUN 2001 TENTANG OTONOMI KHUSUS BAGI PROVINSI PAPUA TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT DI KAMPUNG BUMI MULIA DISTRIK WANGGAR KABUPATEN NABIRE-PAPUA - Petrus Tekege (Yayasan Akrab Pekanbaru, 2018)
The long-term objectives of this study are: (1). To find the level of problems of Implementation of Law No 21 of 2001 on Special Autonomy for Papua Province to improve the welfare of the community in Kampung Bumi Mulia Wanggar District, Nabire Regency. (2). Providing solutions to problem solving to the government through seminar results research activities, and published through the journal. Keywords: Implementation, Otsus and Welfare